Amino Acid Content and Effect of Different Preservation Methods on Some Biochemical Properties in Black Myrtus communis L. Fruits - Cakmak, Meltem; Bakar, Busra; Ozer, Dursun; Karatas, Fikret; Saydam, Sinan (Galenos Publ House, 2023)
In this study, fruits of black Myrtus communis L. were subjected to different preservation methods [frozen, sun and microwave (MW) dried] and, its biochemical properties were examined. All measurements were triplicated. It was observed that the vitamin levels decreased in sun and MW dried samples (p<0.05). On the other hand, total phenolic compounds, flavonoids and antioxidant capacity of fresh and frozen M. communis L. fruits were found to be higher in sun and MW dried fruits (p<0.05). The amount of oxidized glutathione and malondialdehyde (MDA) increased while the amount of ghrelin and reduced glutathione decreased in the dried fruits (p<0.05). Obtained results indicate that, it is rich in terms of vitamins, amino acids, and some elements. These results suggest that the black M. communis L. is a balanced source of amino acids in terms of the total essential amino acid/total amino acid ratio. Experimental findings show that the most suitable preservation method for M. communis L. fruits is freezing. In addition, MW drying seems more advantageous than sun drying in terms of vitamin loss and time.
Keywords: Myrtus communis L; food preservation; phenolic substance; antioxidant capacity; elements; HPLC